Structural Assessment For A Three Storey Building Under Different Usage Using S-Frame - Chin, Wai Yet (Universiti Sains Malaysia, 2005)
Structural analysis is one of the important constituents of structural engineering. This report deal with the effect of increased the area load onto the structural. The purpose of this project is to analyze the structure behavior under different load cases which content 2.0kN/m2 , 2.5kN/m2 , 3.0kN/m2 , 4.0kN/m2 and 5.0kN/m2 . The building is originally for office usage. Tested loading(imposed load)are start from 2.0kN/m² to 5kN/m². From the analysis the critical elements of the structure are obtained. The performance of the building is then analyzed through the relationship between maximum moment and area load. This to prevent any structure failure occurs during the change of structure function. S-Frame version 6.1 is used to model and analyze the structure. A thorough analysis of the building frame, using stiffness, flexibility and finite element methods. To remain the structure safety and reliability, the regular inspections and condition assessment of engineering structures are necessary to ensure that early detection of any defect can be made. From the final result, this structure are fail during the 5.0kN/m², which failed element from second floor of the building.